2018
DOI: 10.1590/1678-5150-pvb-5238
|View full text |Cite
|
Sign up to set email alerts
|

Fotossensibilização primária em bovinos leiteiros causada por Froelichia humboldtiana

Abstract: RESUMO: O presente trabalho foi conduzido com o objetivo de relatar um surto de fotossensibilização causado por Froelichia humboldtiana em bovinos leiteiros no Estado do Rio Grande do Norte, Brasil. Foram examinados animais de uma propriedade rural que apresentavam sintomatologia compatível com fotodermatite. Procedeu-se a coleta de amostras de sangue periférico de cinco bovinos para análise das atividades das enzimas hepáticas gamaglutamiltransferase e aspartatoaminotransferase, além da concentração de bilirr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…However, these plants cause secondary photosensitization, and hepatic injuries can be diagnosed by biopsies or by serum biochemistry analysis. Serum levels profiles of AST, GGT and bilirubin's, are important tools to distinguish primary and secondary photosensitization because elevated concentrations are observed when significant damages are present in the liver (Knupp et al 2014(Knupp et al , 2018. These profiles remain within the normal range in cases of primary photodermatitis (Souza et al 2012, Knupp et al 2016.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, these plants cause secondary photosensitization, and hepatic injuries can be diagnosed by biopsies or by serum biochemistry analysis. Serum levels profiles of AST, GGT and bilirubin's, are important tools to distinguish primary and secondary photosensitization because elevated concentrations are observed when significant damages are present in the liver (Knupp et al 2014(Knupp et al , 2018. These profiles remain within the normal range in cases of primary photodermatitis (Souza et al 2012, Knupp et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…The toxic principle of F. humboldtiana is unknown, but it is suggested that naftodiantrones may be related to the pathogenesis of tegumentary lesions (Pimentel et al 2007). Other toxins from Brazilian plants can be excreted in milk, such as pyrrolizidine alkaloids, steroidal saponins, monocrotaline, ptaquiloside, and tremogenic toxin from Ipomoea asarifolia (Dickinson et al 1976, James 1994, Medeiros & Górniak 1995, Lemos et al 1998, Lopes et al 2014.Therefore, the possibility of F. humboldtiana toxin(s) being excreted by the milk of poisoned cows should be investigated better, since this characteristic was not observed in previous studies in cows (Knupp et al 2018) and dairy goats (Santos et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Froelichia humboldtiana, a plant that causes primary photosensitization in cattle, sheep and goats (Souza et al 2012, Knupp et al 2018, Silva Filho et al 2020 was frequently found in the region, however, few outbreaks of poisonings were reported (four outbreaks in total). This low number of cases probably occurred because F. humboldtiana is less recognized by farmers and veterinarians as the etiology of photodermatitis in ruminants.…”
Section: Discussionmentioning
confidence: 99%